Transplantation of Hearts Donated after Circulatory Death - White, Christopher W.; Messer, Simon J.; Large, Stephen R.; Conway, Jennifer; Kim, Daniel H.; Kutsogiannis, Demetrios J.; Nagendran, Jayan; Freed, Darren H. (Frontiers in Cardiovascular Medicine, 2018)
Cardiac transplantation has become limited by a critical shortage of suitable organs from brain-dead donors. Reports describing the successful clinical transplantation of hearts donated following circulatory death (DCD) have recently emerged. Hearts from DCD donors suffer significant ischemic injury prior to organ procurement; therefore, the traditional approach to the transplantation of hearts from brain-dead donors is not applicable to the DCD context. Advances in our understanding of ischemic post-conditioning have facilitated the development of DCD heart resuscitation strategies that can be used to minimize ischemia-reperfusion injury at the time of organ procurement. The availability of a clinically approved ex situ heart perfusion device now allows DCD heart preservation in a normothermic beating state and minimizes exposure to incremental cold ischemia. This technology also facilitates assessments of organ viability to be undertaken prior to transplantation, thereby minimizing the risk of primary graft dysfunction. The application of a tailored approach to DCD heart transplantation that focuses on organ resuscitation at the time of procurement, ex situ preservation, and pre-transplant assessments of organ viability has facilitated the successful clinical application of DCD heart transplantation. The transplantation of hearts from DCD donors is now a clinical reality. Investigating ways to optimize the resuscitation, preservation, evaluation, and long-term outcomes is vital to ensure a broader application of DCD heart transplantation in the future.